PENYELESAIAN SENGKETA WARIS ADAT PADA MASYARAKAT SUKU DAYAK NGAJU DI KECAMATAN KAHAYAN HILIR KABUPATEN PULANG PISAU PROVINSI KALIMANTAN TENGAH - , Irawan ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this study of was to determine the traditional inheritance dispute to the community of Dayak Ngaju tribe in the district Pulang Pisau province of Central Kalimantan. In addition to know the cause of the dispute Ngaju inheritance to the Dayak community in the District of Pulang Pisau Kahayan Downstream District of Central Kalimantan Province. This research is a sociological jurisdiction, which is a legal research see the law as a phenomenon or social institutions. Primary data in this research is primary data obtained directly from study subjects. To complement the primary data was also conducted research literature. The study subjects consisted of respondent number 15 (fifteen) consisting of 5 (five) people in the villages pulang pisau, 4 (four) people in the village Gohong, 4 (four) people in the village Buntoi and 2 (two) people in the village Anjir. There are also sources that support the research data by providing information on the examined problem. Sources consists of the Kepala Adat Kahayan Hilir Damang and those who know the issue inheritance disputes. The data obtained and analyzed using a qualitative approach and aimed to produce conclusions through logic induktif. The results showed that some of the Dayak Ngaju community in the District Kahayan Hilir perform inheritance dispute resolution, resolve their problems through the judiciary, led by Damang Kepala Adat. Because according to their customary court was enough to give them satisfaction and a sense of fairness in inheritance disputes.